Maintenance Care at Clients With Low Self-Price That Experiences Defisit of Self-Care: Decorating / Dressed In The Berry Room, Duren Sawit Special Hospital, East Jakarta - Supriyono, Ragil; Sitorus, Rusmawati (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
The purpose of this study was to determine nursing care for three respondents (Miss. S, Miss. P and Mrs. R) with self-care deficits, including: assessment, establishing nursing diagnoses, intervention, implementation and evaluation. This research is descriptive with a case study approach, namely by carrying out nursing care for low self-esteem patients starting from assessment, nursing diagnosis, nursing planning, nursing implementation and nursing evaluation and data collection can be carried out for 5 days at the Duren Sawit Regional Special Hospital, Jakarta. East. Data analysis requires further care and collaboration with other medical teams and clients which is indispensable for the success of nursing care. After nursing care results are obtained, the client can build a trusting relationship, the client can recognize the importance of self-care to make up/dress up, the client can make up/dress up with the help of a nurse, the client can make up/dress up independently, the client can maintain make up/dress up independently. independent. The client's nursing problem regarding low self-esteem who has a self-care deficit, basically can be implemented well and most problems can be resolved with the help of the room nurse.